DEVELOPING SUPPLEMENTARY MULTIMEDIA-BASED LISTENING MATERIALS FOR THE SEVENTH GRADERS - isna Rakhmawati; Emalia Iragiliati; Sri Rachmajanti (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2016)
The purpose of this study was to develop supplementary multimedia-based listening materials for seven grade students in second semester using scientific approach Curriculum of 2013. The research design of this study adapted the framework of developmental model by Dick and Carey (2001) with the multimedia-based materials development model by Kinney and Bruck (2009). The final product of this study was in macromedia flash file attached inside CDs/DVDs. The result of product evaluation and try-out showed that the materials were interestingly presented in terms of topics, listening activities and animations. Moreover, it was also able to motivate students to learn listening.   Penelitian ini dilakukan untuk mengembangkan materi menyimak berbasis multimedia sebagai materi tambahan untuk siswa kelas VII SMP pada semester kedua yang menggunakan scientific approach Kurikulum 2013. Penelitian ini mengadopsi model pengembangan Dick dan Carey (2001) dan model pengembangan materi berbasis multimedia oleh Kinney dan Bruck (2009). Produk akhir dari penelitian ini berupa macromedia flash yang dapat diakses melalui CD/DVD. Hasil dari validasi produk serta try-out menunjukkan bahwa materi yang disajikan menarik dari segi topik, ragam aktifitas menyimak dan animasi. Selain itu, materi juga dapat memotivasi siswa untuk belajar menyimak.